IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN PAIBP KELAS VIII-D SMPIT AL-KHAIR BARABAI - Muhammad Rossi (JIP: Jurnal Ilmu Pendidikan, 2025)
SMPIT Al-Khair Barabai is one of the schools in Hulu Sungai Tengah Regency that passed the Third Generation of the School Mover Program, where the school is guided directly by the school mover facilitator for the implementation of the Independent Curriculum including the implementation of differentiated learning. Therefore, the researcher wants to describe the implementation of differentiated learning, especially in the PAIBP subject in class VIII-D, starting from the planning, implementation and evaluation processes. This type of research is field research using descriptive qualitative methods. The data collection techniques used are observation, interviews, and documentation. Data processing is carried out descriptively qualitatively, then described based on the problems that occur in the field. The data sources for this study are PAIBP teachers for class VIII-D, the Deputy Principal for curriculum and several students in class VIII-D. The data analysis techniques used are condentation (summary), data display and conclusion drawing. The data validity test used is editing and triangulation techniques. The results of this study are that teachers use the results of the initial assessment conducted by the BK teacher first, then conduct a curriculum analysis (analysis of basic competencies and learning objectives) then the results of both are used as the basis for compiling differentiated teaching modules/RPP and as a basis for selecting the differentiation strategy used. In learning activities, students are divided into three groups based on learning styles, namely: visual groups, auditory groups and kinesthetic groups, each group is given different learning media and tasks, in the closing activity the teacher provides reinforcement so that students do not misunderstand the concept, reflection and drawing conclusions together. At the evaluation stage, the teacher conducts formative assessments in the form of daily assessments and summative assessments in the form of Mid-Semester Assessments and Final Semester Assessments.